Immersive Cinematic Experience Through Sound Technology in Film: A Systematic Review - Anak Ugap, Catherina; Nazam, Raden Ajeng Kartini Nazam; Hashim, Mohd Ekram Alhafis; Nugrahani, Rahina (Journal of Advanced Research Design, 2025)
Sound technology has a significant influence on audience engagement, emotional resonance, and overall storytelling impact, yet it is often underappreciated and overlooked. As cinema progresses, advances in audio technologies have become crucial to narrative development, providing a dynamic sound backdrop that complements visual storytelling. The objective of this systematic review is to investigate the importance of sound technologies in shaping the immersive film experience and to thoroughly analyze and synthesize current literature on the impact of sound technology in film, including spatial audio, surround sound, and binaural recording techniques. This research seeks to identify patterns, trends, and gaps in current knowledge. The significance of this study lies in its potential to enlighten filmmakers, sound designers, and researchers about the profound impact of sound technology on audience engagement and emotional resonance. This study contributes to the broader discussion on the intersection of technology and storytelling, offering insights that can help shape the future of audiovisual experiences. The findings of this systematic review can inspire future innovations in sound technology, not only in the realm of film but also in industries beyond entertainment, such as virtual reality and augmented reality, by fostering a deeper appreciation for the auditory dimension in the cinematic realm. Lastly, this analysis paves the way for a more holistic understanding of cinematic art, emphasizing the symbiotic relationship between technology and storytelling in the audiovisual landscape.